2018
DOI: 10.1007/s10903-018-0806-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status and Service Assessment for Adult Syrian Refugees Resettled in Metropolitan Atlanta: A Cross-Sectional Survey

Abstract: Because little is known about the mental health status of Syrian refugees in the United States, we conducted a survey among a convenience sample of those resettled in Atlanta between March 2011 and 2017. Though home visits, we delivered a questionnaire including standardized instruments (HSCL25 and PTSD-8) to assess symptoms of anxiety, depression and Posttraumatic Stress Disorder. We found high rates of anxiety (60%), depression (44%) and Posttraumatic Stress Disorder (84%) symptoms; however, only 20% of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 19 publications
3
39
2
Order By: Relevance
“…The 1.5 year follow-up revealed that mental distress does not change significantly over time, and overall remains quite high in comparison to the general population in Germany [42][43][44]. However, compared to other studies with Syrian refugees, the observed prevalence rates of depression, PTSD and anxiety disorder were much lower [11,16]. Experienced traumatic events as well as post-migration factors, such as discrimination or further validity of residence permission were both identified as relevant risk factors for mental disorders.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The 1.5 year follow-up revealed that mental distress does not change significantly over time, and overall remains quite high in comparison to the general population in Germany [42][43][44]. However, compared to other studies with Syrian refugees, the observed prevalence rates of depression, PTSD and anxiety disorder were much lower [11,16]. Experienced traumatic events as well as post-migration factors, such as discrimination or further validity of residence permission were both identified as relevant risk factors for mental disorders.…”
Section: Discussionmentioning
confidence: 80%
“…Besides these traumatic experiences, refugees are also confronted with post-migration stressors in their host countries, such as loss of their social lives, discrimination, poor integration, lack of relevant language and cultural skills, barriers to employment and uncertainty about their asylum status [4,[7][8][9][10]. In a study conducted in the U.S. among Syrian refugees the top three post-migration challenges were identified as being the language barrier, worries about family members back home and inability to pay living expenses [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological stressors were discussed equally among male and female participants. These findings underscore the importance of providers’ awareness of the parental stressors that affect their ability to manage their children’s health and seek help for their children’s illnesses [ 9 , 13 , 31 ]. Beyond the individual provider, systems need to recognize, identify, and act upon these stressors during care encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Syrian refugees in Kentucky have the added stress of resettlement in a new country. Syrians and Syrian refugees have a wide range of mental health problems including but not limited to post traumatic stress disorder (PTSD), anxiety, depression, exacerbation of pre-existing mental health disorders, and experiencing violence, and tremendous loss [39,38,40,41,42]. [38].…”
Section: Discussionmentioning
confidence: 99%